2011
DOI: 10.5755/j01.ee.22.5.969
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Causality Relationship between Renewable Energy Consumption and Economic Growth in Lithuania

Abstract: The topic of the interrelationship between energy consumption and economic growth is widely discussed in scientific literature. Scientists agree that the reason for the interest in such investigations arises because of increased worldwide concern about the impact of energy and environmental policies on the country's economy. Recently, the investigations of causality interrelationships between energy consumption and economic growth have been performed for many countries,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 32 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…Such analysis were performed in (Anwar, Arshed, & Nabeela Kousar, 2017) on a panel of 29 OIC countries, data period 1990-2014; in (Alper, & Oguz, 2016) (Bozkurt, & Destek, 2015) on a panel of OEDC countries, data period 1980OEDC countries, data period -2012in (Tugcu, Ozlturk, & Aslain, 2012) on a panel G-7 countries, in (Okyay, Ebru, & Fatih, 2014) on a panel of developed countries in Europe, data period 1990Europe, data period -2011in (Chontanawat, Hunt, & Pierse, 2008) on a panel of 100 countries, data period 1960-2000 or 1971-2000. Similar studies for the case of individual countries and for different periods of time can be found for Saudi Arabia (Wada, 2017), for China (Lin, & Moubarak, 2014), for Turkey (Ocal, & Aslan, 2013), for Brazil (Pao, & Fu, 2013), for U.S. (Stern, 2000;Yildirim, Sarac, & Aslan, 2012), for Lithuania (Bobinaite, Juozapaviciene, & Konstantinaviciute, 2011).…”
Section: Literature Reviewsupporting
confidence: 74%
“…Such analysis were performed in (Anwar, Arshed, & Nabeela Kousar, 2017) on a panel of 29 OIC countries, data period 1990-2014; in (Alper, & Oguz, 2016) (Bozkurt, & Destek, 2015) on a panel of OEDC countries, data period 1980OEDC countries, data period -2012in (Tugcu, Ozlturk, & Aslain, 2012) on a panel G-7 countries, in (Okyay, Ebru, & Fatih, 2014) on a panel of developed countries in Europe, data period 1990Europe, data period -2011in (Chontanawat, Hunt, & Pierse, 2008) on a panel of 100 countries, data period 1960-2000 or 1971-2000. Similar studies for the case of individual countries and for different periods of time can be found for Saudi Arabia (Wada, 2017), for China (Lin, & Moubarak, 2014), for Turkey (Ocal, & Aslan, 2013), for Brazil (Pao, & Fu, 2013), for U.S. (Stern, 2000;Yildirim, Sarac, & Aslan, 2012), for Lithuania (Bobinaite, Juozapaviciene, & Konstantinaviciute, 2011).…”
Section: Literature Reviewsupporting
confidence: 74%
“…Notable studies of the Lithuanian scientists include more general investigations at macroeconomics level. Bobinaitė et al (2011) assessed the causality relationship between renewable energy consumption and economic growth in Lithuania; Smaliukienė et al (2012) investigated interrelationship between energy consumption and the Lithuanian economic growth; Konstantinavičiūtė et al (2010) examined the dynamic of energy demand; Dudzevičiūtė (2013) did research on economic structural changes and energy consumption.…”
Section: Empirical Studies' Review and Research Methodologymentioning
confidence: 99%
“…In Lithuania, Bobinaite et al [34] examined the linkage between economic growth (GDP) and renewable energy consumption (RES) by employing unit root, co-integration and Granger causality tests. Here, they have found a unidirectional relationship running from RES gross inland consumption to real GDP in the short run.…”
Section: Literature Reviewmentioning
confidence: 99%